Spelling Bee Game in Students’ Vocabulary Achievement - Siti Syafi'atul Qomariyah; Baiq Zuhrotun Nafisah (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2020)
Finding the effect of Spelling Bee Game in students’ vocabulary achievement is aimed in this research. Quasi-experimental with non-equivalent control group design as the research design. The population of the study was the first-grade students of MTs. Darul Qur’an consisted of two classes. The samples were 22 students of VII D class as the experimental group, and 22 students of VII C class as the control group so the total of the sample was 44 students. They were chosen by using the purposive sampling technique. The experimental group was treated by Spelling Bee Game, and the control group was treated by Crossword puzzle Game that is usually used by the teacher. The instrument was a vocabulary test. Then, SPSS was used to analyze the data. 67.8 was the mean score of post-test in the experimental group while 60.8 was the control group and the score of t-test was 2,359 was higher than the score of t-table was 2,021 at the level significance of 5%. It means that the Spelling Bee was the alternative game to teach vocabulary.